ANALISIS PENDAPATAN SEBELUM DAN MASA PANDEMI PADA USAHA TANI SELADA HIDROPONIK (STUDI KASUS: QUEEN FARM DI KOTA PONTIANAK) - Nidya Ramdhani Putri (Institute of Computer Science (IOCS), 2023)
This research aims to analyze the income before and the pandemic that is obtained from business Queen Farm Hydroponics in the city of Pontianak. The research method used is a case study method. This study uses the analysis of quantitative data is collected for three months (quarter) of the last before the pandemic (December, January and February) and three months of pandemic (Maret, April dan Mei). The results showed : the acceptance of the business Queen Farm Hydroponics in the period before the pandemic derived from the sale of fresh vegetables with an average of Rp 7.466.666 per month, while in the pandemic obtained from fresh vegetables with an average of Rp 14.080.000 per month. The advantage before the pandemic average of Rp 6.403.648 per month, while the pandemic Rp12.392.842 per months. Economically this business is categorised in business that is still eligible to run in the period before and the period of the pandemic.